Conceptual Understanding of Students with Special Needs in Two-dimensional Shapes Based on Pirie Kieren's Theory - Jannah, Ukhti Raudhatul; Hafsi, Ainur Rofiq; Nurhidayati, Septia (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2023)
This study aims to describe the conceptual understanding of two-dimensional shapes in students with special needs based on Pirie Kieren's theory in terms of learning motivation. This research is a case study with the research subject is 1 students with special needs of class IV at SDN Pademawu Timur V The results of this study are low learning motivation with layers of understanding on the square starting from Image making then head to property noticing to ineffective folding back to image making and do ineffective folding back again to primitive knowing. In solving the square problem, the subject doubled back to ineffective image-making and primitive knowing. Meanwhile, in the rectangular problem, the subject does one folding back to image making. There are similarities in solving square and rectangular problems, for example, the subject describes the two-dimensional shape first before image making and folding back because they don't know how to calculate the area of a square and rectangle. From the similarities and differences in the thinking flow of students with special needs in squares and rectangles, educators are expected to be able to pay attention to their understanding abilities and learning motivation before carrying out learning.